A Complete Association of an intronic SNP rs6798742 with Origin of Spinocerebellar Ataxia Type 7‐CAG Expansion Loci in the Indian and Mexican Population. (9th June 2017) - Faruq, Mohammed; Magaña, Jonathan J.; Suroliya, Varun; Narang, Ankita; Murillo‐Melo, Nadia M.; Hernández‐Hernández, Oscar; Srivastava, Achal K.; Mukerji, Mitali
Summary: Spinocerebellar ataxia type 7 (SCA7) is a rare neurogenetic disorder caused by highly unstable CAG repeat expansion mutation in coding region of SCA7. We aimed to understand the effect of diverse ATXN7 cis ‐element in correlation with CAG expansion mutation of SCA7. We initially performed an analysis to identify the haplotype background of CAG expanded alleles using eight bi‐allelic single nucleotide polymorphisms (SNPs) flanking an ATXN7 ‐CAG expansion in 32 individuals from nine unrelated Indian SCA7 families and 88 healthy controls. Subsequent validation of the findings was performed in 89 ATXN7 ‐CAG mutation carriers and in 119 unrelated healthy controls of Mexican ancestry. The haplotype analyses showed a shared haplotype background and C allele of SNP rs6798742 (approximately 6 kb from the 3′‐end of CAG repeats) is in complete association with expanded, premutation, intermediate, and the majority of large normal (≥12) CAG allele. The C allele (ancestral/chimp allele) association was validated in SCA7 subjects and healthy controls from Mexico, suggesting its substantial association with CAG expanded and expansion‐prone chromosomes. Analysis of rs6798742 and other neighboring functional SNPs within 6 kb in experimental datasets (Encyclopedia of DNA Elements; ENCODE) shows functional marks that could affect transcription as well as histone methylation. An allelic association of the CAG region to an intronic SNP in two different ethnic and geographical populations suggests a ‐cis factor‐dependent mechanism in ATXN7 CAG‐region expansion.